1997
DOI: 10.1097/00005176-199709000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability in Cystic Fibrosis in Relation to Genotype

Abstract: These data show that the IP in CF was related to patient genotype; those homozygozous or heterozygous for delta F508 having a significantly increased IP compared with patients with unidentified genotypes, who had IP values within the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
2
23
0
1
Order By: Relevance
“…Actual fat absorption is less than intake because, even with enzyme supplementation, 5-20% of dietary fat is not absorbed in persons with CF (25). The ratio of absorbed fat to carbohydrate in CF may be further altered by abnormalities in carbohydrate absorption, because enhanced jejunal absorption of glucose (26) and other sugars (27) has been shown. Thus, the combination of decreased fat and increased glucose absorption in CF may lead to a postprandial metabolic milieu similar to that found in individuals consuming a highcarbohydrate, low-fat diet, and might be an explanation for isolated hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…Actual fat absorption is less than intake because, even with enzyme supplementation, 5-20% of dietary fat is not absorbed in persons with CF (25). The ratio of absorbed fat to carbohydrate in CF may be further altered by abnormalities in carbohydrate absorption, because enhanced jejunal absorption of glucose (26) and other sugars (27) has been shown. Thus, the combination of decreased fat and increased glucose absorption in CF may lead to a postprandial metabolic milieu similar to that found in individuals consuming a highcarbohydrate, low-fat diet, and might be an explanation for isolated hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have suggested that pathological modifications in EFAD may be the consequence of cell adhesion disorders [200]. …”
Section: Intraluminal Abnormalitiesmentioning
confidence: 99%
“…Patients with CF exhibit intestinal inflammation (De Lisle and Borowitz 2013;Werlin et al 2010), and intestinal permeability is also increased (Hallberg et al 1997;van Elburg et al 1996). My lab has shown that increased intestinal permeability also occurs in the widely used mouse model of CF, the Cftr knockout mouse (CF mouse) (De Lisle et al 2011).…”
Section: Introductionmentioning
confidence: 99%